Design of Hamming Code Checker Using Titanium-Diffused Lithium Niobate-Based Waveguide. Issue 4 (4th July 2019) - Srivastava, Vivek Kumar; Pal, Amrindra; Sharma, Sandeep
ABSTRACT: This work presents an electro-optic effect-based design for the widely used Hamming code for checking single bit errors in the received data. The structure is based on Mach-Zehnder Interferometer, designed using Titanium-diffused Lithium Niobate-based waveguides. The proposed device has been successfully tested using the beam propagation method. For a received 7-bit code, the three simultaneously generated check bits are combined to check the error position. Critical performance parameters like extinction ratio (24.39dB), contrast ratio (25.711dB), insertion loss (0.041dB), and amplitude modulation (0.079dB) calculated for the overall device are within acceptable limits for the feasibility of the device.